(untitled) (EU and comparative law issues and challenges series (ECLIC), 2024)
The principle of fairness in EU competition law is examined, specifically with respect to enforcement actions of the EU Commission. Reference to the fundamental elements of fairness (such as transparency, impartiality, proportionality, and the right of defense) in made with reference to both EU legislation and case law. The analysis uncovers several strengths in the current framework and highlights critical weaknesses, including the limited judicial scrutiny of the EU Commission’s complex economic assessments and the principle that post-investigation documents hold less evidentiary weight. It is suggested that current frameworks need refinement. Indications for further research is also specified.